What Do Mining Students Really Need? An ESP Needs Analysis for English for Mining Courses - Heri Alfian; Nasmah Riyani; Litha Nesidekawati Dakka; Assyarifullah Ramli; Dzakiah; Alifiah Pratiwi (The Journal Of English Teaching For Young And Adult Learners, 2026)
English for Specific Purposes (ESP) has been widely recognized as an effective approach to address learners' specific academic and professional needs. In mining education, English is necessary not only for academic purposes but also for safety procedures, technical documentation, and communication in the workplace. However, English for Mining courses in higher education often rely on general English materials that do not fully reflect students' real needs. This makes it hard to understand what students really need. Using a descriptive quantitative design, data from 45 undergraduate mining students were collected via an ESP needs analysis questionnaire. Students' target needs and learning needs, including necessary language proficiency, preferred learning activities, and types of learning materials, were examined in the questionnaire. The results showed that speaking and reading abilities are thought to be the most important for future work environments, especially when it comes to comprehending technical reports, safety guidelines, and oral communication in mining operations. Students also indicated a high preference for hands-on, task-based learning experiences that were connected to actual mining environments. The study comes to the conclusion that authentic materials and workplace-oriented communication challenges should be prioritized in English for Mining courses. The results have useful ramifications for the creation of ESP curricula in mining education.